Soil nutrients and maize responses to elemental sulphur as a fertilizer and soil amendment for bintang series soil - Karimizarchi, Mehdi (2015)
High pH soils accounts for more that 30 percent of world soils. Although the distribution of these soils in Malaysia is not well documented, there are some high pH soils, found all over the country, which are affected by the limestone materials. Alkaline soils pose problems to plant nutrient availability especially micronutrients, in which for each unit increase in soil pH the activity of ferrous iron, Zn, Mn and Cu decreases about 100 times. Increasing the release of indigenous soil nutrients and supplying the plants with external sources of available nutrients are two well-known agronomic approaches for alleviation of these problems. Elemental sulphur as a cheap and readily available source of soil acidulate possess the slow release characteristics that is produced as a by-product of oil refinery may be a useful material for alleviating some alkaline soil problems. The objective of the present project was to evaluate the ability of high pH Malaysian soils to oxidize elemental sulphur and to evaluate selected soil and plant responses to soil acidification using elemental sulphur. In the first study, Bintang Series soils located in Perlis was selected and analyzed for soil physicochemical properties. It was found that the soil was inherently infertile, characterized by low organic matter and nutrient content. Soil was found to be slightly alkaline in nature with the pH value of 7.5 which is affected by limestone materials. The soil was poor in available micronutrients, nitrogen, sulphur and phosphorus that could lead to their shortage for plants. In addition, the total N, S, Cu and Zn in the soil were very low and these nutrients should be applied for long term and sustainable agricultural practices. However the release of indigenous Fe, Mn and K, which were found in high amounts, can be employed to increase their available fraction. Therefore, it is most likely that successful agricultural practices needs addition of soil amendments or fertilizer application to prevent nutrient deficiency.The second study evaluated the ability of Bintang Series soil in oxidation and incorporation of elemental sulphur. To quantify elemental sulphur oxidation and transformations in this soil, it was treated with 6 rates of elemental sulphur and sampled 8 times during 75 days of incubation in laboratory conditions. Results demonstrated that elemental S, applied up to 1 g S kg-1 soil, was successfully biologicaly oxidized and converted to both organic and inorganic forms. While sulphate, as inorganic water soluble S, appeared to be the predominant form in the soil treated with 0.25 g S kg-1 and more, organic forms of S were the major form when the soil was amended with 0.12 g S kg-1 and less. In the third study, the effect of elemental sulphur on urea transformations was elucidated. The results showed that ammonia volatilization was the major pathway and application of elemental sulphur can significantly decrease it from 80 percent at untreated soil to only 30 percent in Bintang Series soil treated with 2 g S kg-1 soil. In the fourth study, after 0, 20 and 40 days of soil incubation with different amounts of elemental sulphur including 0, 0.5, 1 and 2 g S kg-1 of soil, maize plants were grown for 45 days under glasshouse conditions. Plants received 0.5 and 1 g S kg-1 soil showed maximum performance with 45 percent increase in total dry weight. Results of plant analysis revealed that this is due to the increase in S, Zn and Mn content of maize leaves, stem and root from deficient in un-amended to sufficient level in amended plants. Additionally, excessive sulphur addition resulted in Zn and Mn toxicity with 57.5 percent reduction in maize biomass. The results of soil analysis showed that addition of elemental sulphur decreased soil pH and consequently the concentrations of soil nutrients increased. While this resulted in higher concentration of some nutrients, such as S, Mn and Zn, in maize, the Cu, P and Ca content of treated plants were decreased. The results of fifth study that was aimed to elucidate the effect of elemental sulphur on the nutrient release and its relationship with soil pH exhibited that addition of elemental sulphur significantly increased concentration of all nutrients in Bintang Series soil. Additionally, the release and mobility of each nutrients started at specific pH. While that of Ca and Mg started with small increase in acidity, the pH value at which Cu, Fe, Al, Zn and Mn concentration significantly increased are 3.94, 3.94, 5.26, 5.26 and 6.29 respectively. In conclusion, result of studies confirmed the ability of Bintang Series soils in biological oxidation of elemental sulphur. The results also showed that addition of elemental sulphur increased soil nutrient concentration, alleviated S, Mn and Zn deficiency and reduced Ca, P and Cu concentrations in maize. When used in appropriate amounts, 0.5 g S kg-1 soil or 750 kg S ha-1, elemental sulphur can efficiently enhance soil fertility and maize performance by providing macro and micro nutrients for balanced fertilization.